Collective Reparations for Indigenous Communities Before the Inter-American Court of Human Rights - Contreras-Garduño, Diana; Rombouts, Sebastiaan (Utrecht Journal of International and European Law, 2011)
Recent case law from international courts shows an increased willingness to grant collective reparations. This article focuses on how the Inter-American Court of Human Rights has recently been involved in granting a variety of collective reparations to indigenous groups. Moreover, it illustrates the diverse nature of collective reparations, and why there is a need for them.